Bone Morphogenetic Protein‐2 Induces Donor‐Dependent Osteogenic and Adipogenic Differentiation in Human Adipose Stem Cells. (22nd October 2015) - Vanhatupa, Sari; Ojansivu, Miina; Autio, Reija; Juntunen, Miia; Miettinen, Susanna
Abstract : The effects of bone morphogenetic protein‐2 (BMP‐2) on SMAD1/5 signaling, proliferation, and differentiation in human adipose stem cells (hASCs) were analyzed. BMP‐2 induced dose‐dependent activation of SMAD signaling and decreased proliferation in all the cell lines studied. Furthermore, depending on the hASC donor line, BMP‐2 also induced osteogenic and adipogenic differentiation in hASCs. Abstract : Bone morphogenetic protein‐2 (BMP‐2) is a growth factor used to stimulate bone regeneration in clinical applications. However, there are contradicting reports on the functionality of BMP‐2 in human adipose stem cells (hASCs), which are frequently used in tissue engineering. In this study, we analyzed the effects of BMP‐2 on SMAD1/5 signaling, proliferation, and differentiation in hASCs. Our results indicated that BMP‐2 induced dose‐dependent (25–100 ng/ml) activation of SMAD signaling. Furthermore, the cell proliferation analysis revealed that BMP‐2 (100 ng/ml) consistently decreased the proliferation in all the cell lines studied. However, the analysis of the differentiation potential revealed that BMP‐2 (100 ng/ml) exhibited a donor‐dependent dual role, inducing both osteogenic and adipogenic differentiation in hASCs. The quantitative alkaline phosphatase (qALP) activity and mineralization levels were clearly enhanced in particular donor cell lines by BMP‐2 stimulus. On the contrary, in other cell lines, qALP and mineralization levels were diminished and the lipid formation was enhanced. The current study also suggests that hASCs have accelerated biochemical responsiveness to BMP‐2 stimulus in human serum‐supplemented culture medium compared with fetal bovine serum. The production origin of the BMP‐2 growth factor is also important for its response: BMP‐2 produced in mammalian cells enhanced signaling and differentiation responses compared with BMP‐2 produced in Escherichia coli . These results explain the existing contradiction in the reported BMP‐2 studies and indicate the variability in the functional end mechanism of BMP‐2‐stimulated hASCs. Significance: This study examined how bone morphogenetic protein‐2 (BMP‐2) modulates the SMAD signaling mechanism and the proliferation and differentiation outcome of human adipose stem cells (hASCs) derived from several donors. The results indicate that BMP‐2 triggers molecular SMAD signaling mechanisms in hASCs and regulates differentiation processes in human serum‐culture conditions. Importantly, BMP‐2 has dual activity, inducing osteogenic and adipogenic differentiation, subject to hASC donor line studied. These findings explain contradictory previous results and highlight the importance of further studies to understand how signaling pathways guide mesenchymal stem cell functions at the molecular level.